Brown's framework of EFL teaching principles and how to implement it in EFL classes - Al-Qutaiti, Yaqoub; Sheikh Ahmad, Ismail; Mohin, Mohaida (IMPACT Journals, 2022)
Brown’s (2007) framework of EFL teaching consists of twelve principles of CLT and motivation, as well as Krashen’s ideas of acquisition and learning, and Schumann’s notion of acculturation. This framework is designed for understanding and working with the complexity and multidimensionality of second language teaching. Brown’s book “Principles of language learning and teaching”, (2007) conveys contemporary pedagogical thinking into the EFL context and ESL thinking. Brown offers one of the best-known current accounts of pedagogical principles and methods of second language learning and acquisition. Brown (2007) classified the twelve principles into three sets of principles: Cognitive Principles, Socio-affective Principles and Linguistic Principles. They have permeable boundaries which mean it is difficult to keep each category in complete isolation. These principles form an interactive approach to language teaching.